DOES FINANCIAL LITERACY MODERATE CASHLESS PAYMENT ON MSME PERFORMANCE? - Syaranamual, Shinta; Engko, Cecilia; Gainau, Paskanova Christi (Journal Accounting International Mount Hope, 2025)
This study aims to determine the effect of cashless payment on MSME's performance with financial literacy as a moderating variable in Ambon City. This quantitative descriptive research uses questionnaires and statistical data measured on a Likert scale. The respondents of this study are MSMEs in the culinary field in Ambon City, with a sample of 100. The data sampling uses a purposive sampling technique. Data analysis uses Smart PLS software version 4.0. The study results show that cashless payment has a positive and significant effect on MSME's performance, and financial literacy does not have a positive and significant moderating effect on cashless payment on MSME's performance. Keywords: Cashless Payment, Financial Literacy, MSMEs Performance